Pengaruh Gaya Kepemimpinan Transformasional, Latar Belakang Pendidikan Dan Pengalaman Kerja Terhadap Kinerja Pegawai (Pada Kantor Dinas Lingkungan Hidup Kota Malang ) - Rustam efendi; Hadi Sunaryo; Budi Wahono (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
ABSTRACT            Purpose of the study: To find out how the description of transformational leadership style, educational background, influential work experience and performance of the Malang city environmental department office staff. To find out how the transformational leadership style, educational background and work experience together influence the performance of the Malang city environmental department office.            By using a sample of Malang city environmental department office employees, the results of this study show the variables of transformational leadership style, educational background and work experience together affect the performance of Malang city office environment department employees. Transformational leadership style influences the performance of Malang city environment office staff. The educational background does not affect the performance of the Malang city environmental department office staff. Work experience has no effect on the performance of Malang city environmental service office employees. The leader of the Malang city environmental office, must pay attention to the transformational leadership style, to improve the performance of the Malang city environmental department office employee.Keywords: Transformational Leadership Style, Educational Background and Work Experience on Employee Performance.